Spreading awareness on sustainable development: International Islamic University Malaysia (IIUM) as a model - Elshobake, Mohammed R. M. (BERNAMA, 2024)
Sustainable Development Goals (SDGs), established by the United Nations in 2015, serve as a blueprint for achieving a better and more sustainable future for all. With 17 interconnected goals addressing global challenges such as poverty, inequality, climate change, and environmental degradation, the SDGs provide a framework for collective action at local, national and international levels. In the global pursuit of sustainable development, educational institutions play a pivotal role in shaping the minds of future leaders and change-makers. Among these institutions, the International Islamic University Malaysia (IIUM) stands out as a model for spreading awareness and fostering understanding of sustainable development goals (SDGs). Through its curriculum, research initiatives and community engagement efforts, IIUM exemplifies the significance of teaching SDGs courses in higher education. International Islamic University Malaysia is a distinguished model in the pursuit of implementing the sustainable development goals using Maqasid Syariah as its foundation. It is an international award-winning institution for sustainability. In translating its agenda into a concrete action plan, IIUM has introduced sustainable development courses, the most important course being SCSH1201: Sustainable Development Issues, Principles and Practices. It aims to set a foundation for students to understand the concept and principles of sustainable development.